Cytotoxicity extract and fraction of knobweed (Hyptis capitata) and its effect on migration and apoptosis of T47D cells (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. To’bungan N, Pratiwi R, Widyarini S, Nugroho LH. 2021. Cytotoxicity extract and fraction of knobweed (Hyptis capitata) and its effect on migration and apoptosis of T47D cells. Biodiversitas 23: 572-580. Hyptis capitata Jacq. has an ethnobotanical history. The leaves and stems of H. capitata have been reported to have potential anticancer properties. This study was conducted to determine the anticancer potential of the roots, stems, leaves, and flowers of H. capitata. Organs of H. capitata were extracted in stages using chloroform and continued with methanol to obtain eight extracts. Crude extracts were tested for cytotoxicity on T47D and WiDr cells with the MTT method. Potential inhibition of cell migration by potential fraction was tested with scratch wound healing assay and the content of secondary metabolites was analyzed with gas chromatography-mass spectrometry (GC-MS). An Annexin V-Pl apoptosis test was performed to determine the number of living cells, necrosis, and apoptosis. The results showed that the root chloroform extract showed the highest cytotoxic activity against T47D cells (34.90 ± 4.78µg/mL) and WiDr (44.65 ± 12.07 µg/mL), and it was referred to as a potential extract. Fractionation of the root chloroform extract resulted in four fractions (F1, F2, F3, and F4). Fraction F2 had the highest cytotoxic activity (13.8 ± 0.65 µg/mL) and was selective against T47D cells (selectivity index 3.71). Fraction F2 showed its antimetastatic and apoptotic potential against T47D cells. Gas chromatography-mass spectrometry analyses combined with library showed that the root chloroform extract and fraction F2 contain ferruginol, campesterol, and stigmasterol.
Keywords: Apoptosis, cytotoxicity, knobweed, metastasis, T47D